Open Problems in the Area of Computational Geometry. - Pinciu, Valeriu (2012)
Dr. Pinciu engaged in collaborative research with T.S. Michael from the U.S. Naval Academy focusing on visibility problems, known as art gallery (polygon interior), fortress (polygon exterior), and prison yard (polygon interior and exterior) problems. The outcome resulted in two conference presentations and an article accepted for publication, with additional presentations and another article to follow.
Keywords: dept.mat; faculty_collection; sabbatical_report